Improve of Water Flow Acceleration in Darrieus Turbine Using Diffuser NACA 11414 2,5R - Nugroho, Setyo; Safitra, Arrad Ghani; Aribowo, Teguh Hady; Julianto, Mochammad Arief (EMITTER International Journal of Engineering Technology, 2018)
Indonesia has potential hydro energy around 70000 MW which has been used around 6% (3529 MW). One of the development constraint is the stream velocity in Indonesian rivers is relative low. It causes bigger turbine dimension needed to achieve power which is desired. Â An alternative is to utilize adiffuser, which is a device that could accelerate the fluid flow in order to give more energy to the turbine. Based on contiunity equation, diffuser can increase velocity by ratio of cross-section area. It can be Â used to achieve expected power as long as it is not too much reduce the pressure. This research is conducted in 0.566 m/s of water velocity with Darrieus turbine with hydrofoil NACA 0018, height 0.74 m, radius 0.17 m, chord 0.11 m and 3 number of blades. The performance (Cp) was determined by numerical and experimental without and with diffuser NACA 11414 2.5R for variation of angle 8o, 16o, and 20o. Both of those result showed that the best performance of NACA 11414 2,5R is on angle 16o which numerically has stream velocity 0,91 m/s of water and 7 times of Cp, while experimentally has 0,891 m/s of water velocity and 3,16 times of Cp. This diffuser could improve the power generated by the turbine and increase the turbine efficiency.